An Efficient Synthesis of Pyrido[2, 3‐d][6, 5‐d]dipyrimidine and 5, 5′‐Arylmethylenebis(2, 6‐diaminopyrimidinone) Derivatives under Microwave Irradiation. (23rd October 2013) - Lin, Zhilan; Hu, Huiling; You, Xinkui; Zhang, Xueli; Gao, Yuan
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>